Clinical, immunological, anti-inflammatory and antioxidant roles of zinc - Prasad, Ananda S. (Experimental gerontology, 2008)
The essentiality of zinc for humans was recognized only 40 years ago. Zinc deficiency was suspected to occur in Iranian patients with growth retardation, hypogonadism in males, hepato-splenomegaly, rough and dry skin, geophagia and severe iron deficiency anemia. Later we documented zinc deficiency in similar patients in Egypt. The diet of these patients consisted of mainly cereal proteins which contained high phytate and this led to decreased availability of iron and zinc. These patients had severe immune dysfunctions, inasmuch as they died of intercurrent infections by the time they were 25 years of age. In our studies in experimental human model of zinc deficiency, we documented decreased serum testosterone level, oligospermia, severe immune dysfunctions mainly affecting T helper cells, decreased serum thymulin activity hyperammonemia, neuro-sensory disorders and decreased lean body mass. The basic mechanisms of zinc action on immune cells have been reviewed in this paper. Our studies showed that the activation of many zinc dependent enzymes and transcription factors were affected adversely due to zinc deficiency. The gene expression and production of Th1 cytokines were affected adversely due to zinc deficiency. Zinc is also an antioxidant and has anti-inflammatory actions. We have reported decreased plasma zinc, increased plasma oxidative stress markers and increased generation of inflammatory cytokines in the elderly subjects which were corrected by zinc supplementation. In cell culture studies, we have observed that zinc induces A20 which inhibits NF-κB activation resulting in decreased generation of inflammatory cytokines.